Visible-light photoredox catalyzed synthesis of pyrroloisoquinolines via organocatalytic oxidation/[3 + 2] cycloaddition/oxidative aromatization reaction cascade with Rose Bengal - Vila, Carlos; Lau, Jonathan; Rueping, Magnus (Beilstein Journal of Organic Chemistry, 2014)
Pyrrolo[2,1-a]isoquinoline alkaloids have been prepared via a visible light photoredox catalyzed oxidation/[3 + 2] cycloaddition/oxidative aromatization cascade using Rose Bengal as an organo-photocatalyst. A variety of pyrroloisoquinolines have been obtained in good yields under mild and metal-free reaction conditions.
Keywords: alkaloids; [3 + 2] cycloaddition; organocatalysis; oxidation; photochemistry; photoredox catalysis; Rose Bengal; visible-light